An empirical analysis on leadership styles and the role of organizational culture on employees’ satisfaction in Malaysian hotel industry / Norwahidah Abd. Wahid - Abd. Wahid, Norwahidah (2014)
The topics of leadership and organizational culture have fascinated considerable awareness from both academics and practitioners. The study examined the relationship of leadership style and organizational culture with employee satisfaction in the Malaysian hotel industry. As leadership style is a critical element in the success of an organization, organizational culture is also a crucial factor influencing the competitive strength of an organization. A large amount of the interest in the two areas is based on explicit and implicit claims that both leadership and culture are linked to employees’ satisfaction. Although the links between leadership and performance and between culture and job satisfaction have been looked into separately, few studies have examined the correlation between the three concepts. The research also examined the leadership style used by hotel managers and the perceptions of that leadership practices by the employees relative to their job satisfaction. As for this research, two leadership style were studied (transactional and transformational leadership style) and organizational culture will be mediating the relationship between leadership style and employees’ satisfaction. Organizational culture in the research perspective is defined as a common set of values and beliefs that are shared by members of an organization which influences how people perceive, think, and act. The independent variables are transactional and transformational leadership style was measured using an adapted Multifactor Leadership Questionnaire, the organizational culture as the mediating variable was measured using adapted Denison Organizational Culture Survey. The dependent variable, employees’ satisfaction, was also measured using the adapted Multifactor Leadership Questionnaire. Data were collected from 300 employees from 4 and 5 star rating hotels in Klang Valley and Selangor. Four research questions along with six hypotheses were tested. The finding of this research indicated that employees’ satisfaction is significantly related to the transactional leadership style used by the hotel manager. Furthermore, the research also identify that the nature of this relationship and presents empirical evidence indicated that the relationship between leadership style and employee satisfaction is mediated by the form of organizational culture that is present. Finally, the basis of this research was supported through an extensive literature review, followed by a statistical analysis to suggest conclusion and recommendation for future research.